2017
DOI: 10.1097/bor.0000000000000391
|View full text |Cite
|
Sign up to set email alerts
|

Silicone breast implants and autoimmune rheumatic diseases: myth or reality

Abstract: SBIs are associated in a proportion of patients with complaints such as fatigue, cognitive impairment, arthralgias, myalgias, pyrexia, dry eyes and dry mouth. Silicones can migrate from the implant through the body and can induce a chronic inflammatory process. Explantation of SBI results in the majority of patients in an amelioration of the symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 49 publications
0
67
0
11
Order By: Relevance
“…These compounds significantly elicit immune system activation and responses, leading to tissue alterations and injuries. Different studies have shown that silicone breast implants (SBIs) may be associated to fatigue, cognitive impairment, arthralgias, myalgias, pyrexia, dry eyes and dry mouth [28][29][30]. A robust proof of this is given by the fact that removing SBIs leads to amelioration of the symptoms [31].…”
Section: Discussionmentioning
confidence: 99%
“…These compounds significantly elicit immune system activation and responses, leading to tissue alterations and injuries. Different studies have shown that silicone breast implants (SBIs) may be associated to fatigue, cognitive impairment, arthralgias, myalgias, pyrexia, dry eyes and dry mouth [28][29][30]. A robust proof of this is given by the fact that removing SBIs leads to amelioration of the symptoms [31].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous publications in the past five years have supported the assertion that silicone gel-filled breast implants are genuinely capable of causing a novel systemic illness (1,2,3,4,5,6,7) . Prior claims of a similar nature existed in the 1990's when the controversy first swirled around this issue, but legitimacy at that time was elusive due to faulty methodologies utilized by many investigators (1,4) .…”
Section: Introductionmentioning
confidence: 98%
“…Heavy metals adversely affect enzymes, DNA, and leukocyte respiration; can be toxic to muscle, brain, lungs, kidneys, liver, blood, and nerves; and when present in excess amounts can mimic multiple sclerosis, Parkinson's, Alzheimer's, and muscular dystrophy (21) . Clinical correlates reported in implant recipients include (but are not limited to) hair loss, recurrent infections in a variety of sites, weakness, fatigue, muscle twitching, nail cracking and splitting, cognitive dysfunction, a multitude of other nervous system disorders (e.g., paresthesias; dysesthesias; dizziness; gait imbalance); and abdominal pain, nausea, constipation, and loose stools from dysfunction of the myenteric plexus) (1,2,3,4,5,6,7,12,16,20,22) . i.…”
Section: Illness In Implant Recipientsmentioning
confidence: 99%
See 2 more Smart Citations